Informed Consent Forms for Research with Human Subjects: Time to End the Charade - Glantz, Leonard H (American journal of law & medicine, 2024)
In 1974, the Center for Law and Health Sciences at the Boston University School of Law provided legal background papers on informed consent to research to the newly created National Commission for the Protection of Human Subjects of Biomedical and Behavioral Sciences. These papers were written by George J. Annas, the Center's Director, as well as Barbara F. Katz and I, who were staff attorneys at the time. These papers can be found in the appendices to the Commission reports and in our book , in which we present a refined version of those papers. This project introduced me to the world of human research ethics and the complexities of protecting the rights and welfare of research subjects. Over the past fifty years, I have sat on Institutional Review Boards (IRBs), been a member of the FDA's Pediatric Research Advisory Board, and engaged in varying activities related to human subject protection. During this time, I took for granted that consent forms were the best method for ensuring that subjects were thoroughly informed about all aspects of the proposed research. Like many IRB members, I spent considerable time reviewing, editing, and debating with other IRB members about the precise wording of these forms.